[tex]a)[/tex] [tex](7 * 10^{6} ) * ( 1,1 * 10^{5} ) = 7,7 * 10^{6+5} = 7,7 * 10^{11}[/tex]
[tex]b)[/tex] [tex](2 * 10^{-8} ) * (3,8 * 10^{6} ) = 7,6 * 10^{-8 + 6} = 7,6 * 10^{-2}[/tex]
[tex]c)[/tex] [tex](9,6 * 10^{-7} ) * (2 * 10^{-2} ) = 19,2 * 10x^{-7 + (-2)} = 19,2 * 10^{-9} = 1,92 * 10^{-8}[/tex]
[tex]d)\\[/tex] [tex](4 * 10^{10} )^{3} = 4^{3} * 10^{10 * 3} = 64 * 10^{30} = 6,4 * 10^{31}[/tex]
[tex]e)[/tex] [tex](0,8 * 10^{-8} )^{2} = 0,8^{2} * 10^{-8 * 2} = 0,64 * 10^{-16} = 6,4 * 10^{-17}[/tex]